The organizational climate relevance in organizations (Research, Society and Development, 2021)
This article discusses reflections on the organizational process in the business environment in order to reflect on the well-being of employees in the work environment. The research proposed here has as a problem the way the organizational climate can interfere in the quality of life of employees. Prepared based on the studies of Chiavenato (2005), Graça (1999), Oliveira (2011), Rizatti (2002) and Russo (2010) who developed studies on organizational climate in organizations, employee well-being and work environment. Bibliographic research was adopted as a methodological technique. In this sense, it is possible to observe that a solid organizational culture, with established values, contributes positively in the construction of the subject before an organization. Therefore, the worker needs a differentiated planning to carry out his activities and that enable the employee to perform better so that he can reach his main objective in the respective company.